The Application of The Rule of Three to Improve The Skill of Writing Children's Story Plots by PGSD Students of Al-Washliyah Archipelago Muslim University Medan - Tiflatul Husna; Putri Juwita; Fita Fatria (Westscience Press, 2024)
This research aims to improve children's story plot writing skills using the rule of three in FKIP PGSD students at Al Washliyah This research aims to improve children's story plot writing skills using the rule of three in FKIP PGSD students at Al Washliyah Muslim Nusantara University, Medan. Remembering that children's stories are an important part of the process of learning Indonesian language and literature in elementary school. The research method used in this research is a quantitative descriptive method with a one group pre-test post-test design type of research. The population and sample in this research were students of the Elementary School Teacher Education Study Program (PGSD) FKIP Al Washliyah Muslim Nusantara University. The population was 50 people and samples were taken using random sampling technique as many as 30 students. From the research results, it is known that the average score of class 5 A PGSD UMN Al Washliyah students in the initial pre-cycle condition was only 55.84%. After taking action in cycle I, student learning outcomes increased to 61.6%. To get better results, action was taken in cycle II. In this cycle student learning outcomes increased to 80.25%. From this it can be said that applying the rule of three in writing children's story plots can improve children's story plot writing skills for semester 5 A students of FKIP PGSD UMN Al Washliyah, Medan. The output targets in this research are national/international journals or proceedings.